Pre-Operative Enhanced Recovery After Surgery (ERAS) Protocol Compliance Towards Major Surgery Patients at Dr. Soetomo General Hospital, Surabaya - Ahmad Sabili Rifa'i; Vicky Sumarki Budipramana; Gadis Meinar Sari (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: The implementation of ERAS protocol can optimize patients after surgery, which in turn can reduce burdens both for patient and hospital. The purpose of this study is to describe the compliance and consistency of ERAS in the pre-operative period of surgery patients in Dr. Soetomo General Hospital Surabaya. Methods: We conducted consecutive observation of major surgical patients for 4 weeks. The type of surgery observed was digestive, thoracic and cardiovascular, and gynecological surgery. The pre-operative period will be calculated for compliance based on the ERAS international protocol. All data of compliance presented descriptively.s.Results: A total of 36 major surgery patients of which 7 (19,4%) were digestive surgeries, 14 (38,9%) were thoracic and cardiovascular surgeries, and 15 (41,7%) were gynecological surgeries. Overall compliance of the ERAS protocol in the pre-operative period of major surgery patients was 91%. The compliance of ERAS protocol in the pre-operative period of digestive surgery patients was 80%, in thoracic and cardiovascular surgery patients was 93,4% and gynecologic surgery patients was 84.3%. Major surgery patients with ≥90% compliance was 25%. Digestive surgery patients with ≥90% compliance was 0%. Thoracic and cardiovascular surgery patients with ≥90% compliance was 64,3%. Gynecologic surgery patients with ≥90% compliance was 0%.Conclusion: : Pre-operative elements of ERAS protocol in major surgery including digestive, thoracic and cardiovascular, and gynecologic surgery in Dr. Soetomo General Hospital, Surabaya needs to be improved.